Frequency of Fetomaternal Outcomes Among Pregnant Women Presenting with Thrombocytopenia : Pregnancy Outcomes in Thrombocytopenic Women - Niaz, Fardous; Sabir, Farzana; Ali, Ahmed; Parveen, Saima; Khadim, Madiha; Madiha, . (Pakistan Journal of Health Sciences, 2026)
Thrombocytopenia is a prevalent hematological disease during pregnancy that may cause fetomaternal adverse outcomes. It is imperative to know its prevalence and the complications associated with it so that it can be identified and dealt with at a very early stage. Objective: To determine the frequency of fetomaternal outcomes among pregnant women with thrombocytopenia. Methods: A descriptive cross-sectional study was done in the Department of Obstetrics and Gynecology, Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur, AJ and K, among 151 pregnant women diagnosed with thrombocytopenia. Patients were also classified according to the severity. The outcomes of the mothers were measured in terms of preeclampsia, HELLP syndrome, placental abruption, and preterm birth. The low birth weight and preterm birth were among the fetal outcomes. Analysis of data was done through SPSS version 25.0. Results: The 151 participants presented the highest number of mild thrombocytopenia, 83(54.9%), moderate 40(26.4%), and severe thrombocytopenia 28(18.5%). Preeclampsia occurred in 54 (35.8%) of cases, HELLP syndrome in 15 (9.9%), and placental abruption in 3 (2.0%). Preterm birth was observed in 15 (9.9%) and low birth weight in 6 (4.0%) of neonates. Maternal and fetal outcomes showed no statistically significant differences across thrombocytopenia severity groups (P-value >0.05). Conclusions: Thrombocytopenia in pregnancy was predominantly mild to moderate in severity, with generally favorable maternal and fetal outcomes. No statistically significant differences were observed across severity groups. Early identification and careful monitoring may help optimize maternal and neonatal care.